Critical Thinking Skills in Socratic Learning - Aulia Putri Timur; Iyon Maryono; Riva Lesta Ariany (UIN Sunan Gunung Djati Bandung, 2022)
The aim of this study was to determine the implementation of the Socratic method on mathematics learning and relevance in developing critical thinking skills. This research used the library research method. The results showed that the Socratic method can develop critical thinking skills including: (1) the questions in the Socratic method made students have curiosity and self-confidence that could construct critical thinking skills; (2) the Socratic method can bring up indicators of critical thinking skills; (3) the Socratic method can practice the ability to question everything so that it can develop critical thinking skills; and (4) the Socratic method can help students find their own preferences in various problems that can make the quality of critical thinking vary